2016
DOI: 10.1017/cem.2015.112
|View full text |Cite
|
Sign up to set email alerts
|

Reported provision of analgesia to patients with acute abdominal pain in Canadian paediatric emergency departments

Abstract: Objectives: Evidence exists that analgesics are underutilized, delayed, and insufficiently dosed for emergency department (ED) patients with acute abdominal pain. For physicians practicing in a Canadian paediatric ED setting, we (1) explored theoretical practice variation in the provision of analgesia to children with acute abdominal pain; (2) identified reasons for withholding analgesia; and (3) evaluated the relationship between providing analgesia and surgical consultation. Methods: Physician members of Pae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…6,12,16 Interestingly, a recent survey of Canadian physicians, including those trained in pediatric emergency, pediatrics, emergency, and family medicine, demonstrated substantially higher self-reported rates of analgesic provision in pediatric appendicitis as compared to our findings. 20 In a case of suspected appendicitis, 92.1% of survey respondents reported that they would offer immediate analgesia. Fifty-eight percent reported that they would offer an IV opioid analgesic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,12,16 Interestingly, a recent survey of Canadian physicians, including those trained in pediatric emergency, pediatrics, emergency, and family medicine, demonstrated substantially higher self-reported rates of analgesic provision in pediatric appendicitis as compared to our findings. 20 In a case of suspected appendicitis, 92.1% of survey respondents reported that they would offer immediate analgesia. Fifty-eight percent reported that they would offer an IV opioid analgesic.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-eight percent reported that they would offer an IV opioid analgesic. 20 This may reflect social desirability bias due to self-reporting, 21 or patient refusal of analgesia. The discrepancy between self-reported rates of analgesia provision and the directly observed rates of analgesia provision suggest that providers are likely aware of the need to provide analgesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this has not been explored to date, current evidence suggests that caregivers harbour concerns surrounding harm, 13 as well as the addictive potential 11,14 of analgesics. In addition, a discrepancy exists between survey data on the high clinicianreported use of analgesia 15,16 and institutional audits of practice patterns that suggest otherwise. 17,18 If the refusal of analgesia were identified as a barrier to adequate pain management for children, it would provide a compelling rationale for the development of educational strategies directed at dispelling misconceptions and encouraging acceptance of analgesia offered in the ED.…”
Section: Introductionmentioning
confidence: 99%
“…Acute abdominal pain is a common cause of suffering and discomfort for children in the pediatric emergency department (ED) (Fein et al, 2012). Numerous studies have shown that children with acute abdominal pain are undertreated for pain in the ED (Kim et al, 2003;Goldman et al, 2008;Poonai et al, 2016). Acute appendicitis is the most common surgical cause of acute abdominal pain in the pediatric ED; and, administering analgesia has been shown to not impede the diagnosis of appendicitis nor increase the incidence of appendicitis-related complications (Kim et al, 2002;Bailey et al, 2007;Furyk and Sumner, 2008;Poonai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%